(untitled) (Global Journal of Management and Business Research, 2015)
This paper intends to discuss and understand contemporary branding techniques in marketing that can influence current consumer buying behavior. By thoroughly examining and understanding the way consumers feel about and perceive brands that influence their buying decisions, companies can adapt to the particular markets they are trying to serve, and promote their brand products using the most suitable branding techniques for their brand that would serve the customers’ interests.